Investigation of the Stellar Population of Several Polar Ring Galaxies - Liliya Shalyapina (Galaxies, 2016)
We present results of our investigation of two multi-spin galaxies which were taken from the catalog of polar ring galaxies. All of them possess nucleus-like knots. An analysis of gas and stars kinematics and study of the stellar population were carried out for these objects. A complex structure and peculiar kinematics of both components were revealed. The observed distribution of the stellar age and metallicity in central parts of galaxies (radius is about 8″) and along directions through their knots helps us to understand the merging processes and make conclusion of the knots’ nature in these objects.